Stable Expression of mtlD Gene Imparts Multiple Stress Tolerance in Finger Millet - Hema, Ramanna; Vemanna, Ramu S.; Sreeramulu, Shivakumar; Reddy, Chandrasekhara P.; Senthil-Kumar, Muthappa; Udayakumar, Makarla (PLOS ONE, 2014)
Finger millet is susceptible to abiotic stresses, especially drought and salinity stress, in the field during seed germination and early stages of seedling development. Therefore developing stress tolerant finger millet plants combating drought, salinity and associated oxidative stress in these two growth stages is important. Cellular protection through osmotic adjustment and efficient free radical scavenging ability during abiotic stress are important components of stress tolerance mechanisms in plants. Mannitol, an osmolyte, is known to scavenge hydroxyl radicals generated during various abiotic stresses and thereby minimize stress damage in several plant species. In this study transgenic finger millet plants expressing the mannitol biosynthetic pathway gene from bacteria, mannitol-1-phosphate dehydrogenase (mtlD), were developed through Agrobacterium tumefaciens-mediated genetic transformation. mtlD gene integration in the putative transgenic plants was confirmed by Southern blot. Further, performance of transgenic finger millet under drought, salinity and oxidative stress was studied at plant level in T1 generation and in T1 and T2 generation seedlings. Results from these experiments showed that transgenic finger millet had better growth under drought and salinity stress compared to wild-type. At plant level, transgenic plants showed better osmotic adjustment and chlorophyll retention under drought stress compared to the wild-type. However, the overall increase in stress tolerance of transgenics for the three stresses, especially for oxidative stress, was only marginal compared to other mtlD gene expressing plant species reported in the literature. Moreover, the Agrobacterium-mediated genetic transformation protocol developed for finger millet in this study can be used to introduce diverse traits of agronomic importance in finger millet.